Synonymization of the name Cathetus roeperianus (Phyllanthaceae) with an emended description and lectotypification of Cathetus fasciculata from the collections of India - Kemprai, Kapil Kumar; Basumatary, Kshiprativ; Borah, Souravjyoti (Phytotaxa, 2025)
The Indian species Cathetus roeperianus is synonymized under Cathetus fasciculata. The species is reported in this communication as an addition to the Flora of Assam, India. Nomenclatural treatment, taxonomic enumeration and an emended description of the species are provided along with colored images and SEM images of the seeds for aid in identification and further studies. Lectotype for the name Cathetus fasciculata is designated here as the name was published without mentioning the type.